A Review of Problems in Legal Interpreting - LYSENKO, Olga A.; BARBAKOV, Oleg M. (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
As exemplified by pressing challenges in justice systems of countries of the former Yugoslavia, the paper presents court interpreting as a category in law and as a tool of government regulation or industrial self-regulation in translation activities. The science merit, applied relevance and scientific novelty of the research in the authors’ approach to comprehension of the issue, firstly, depend on a lack of such regulation in the national (Russian) practice. Secondly, in the law, there is no category or concept of court interpreters in the Russian legal framework. Thirdly, the paper presents a wide review of oversees periodicals as a source database for the research. Using cases from the today’s court interpreting, we have reported changes to the political and linguistic context, as well as the legal context. Governments in these countries have been still considering it difficult and unable to cope in a proper way with the challenges that occurred and the changed needs, so that, according to the European standards, to provide citizens with an equal and non-discriminatory access at home and work environments. This relates both to law-making and actual law enforcement of legal regulations that have been previously drafted and approved.
Keywords: court interpreting, translating, the Balkans, interpreter, legal interpreting, justice reform